Model-based feedforward register control of roll-to-roll web printing systems. (June 2016) - Chen, Zhihua; Zheng, Ying; Zhou, Minjing; Wong, David Shan-Hill; Chen, Lijuan; Deng, Zhonghua
Abstract: Roll-to-roll (R2R) printing press provides a continuous printing process to print the multi-color patterns onto a web. To correctly print patterns on webs without the register error, it is necessary to regulate the web tension and transport velocity. In this paper, a mathematical model is built for R2R web printing system, and a model-based feedforward PD (MFPD) control method is proposed to reduce the effects of interaction in adjacent print units whose print cylinders are driven by electrical line shafts and is compared with other control methods. The proposed control method is applied to an industrial 7-color gravure printing register system. The register error can be controlled in the range of ±0.1 mm at a steady high speed, which meets the requirement of modern industrial application.